2022
DOI: 10.1038/s41598-022-06209-4
|View full text |Cite
|
Sign up to set email alerts
|

Sleep improvements on days with later school starts persist after 1 year in a flexible start system

Abstract: Early school times fundamentally clash with the late sleep of teenagers. This mismatch results in chronic sleep deprivation posing acute and long-term health risks and impairing students' learning. Despite immediate short-term benefits for sleep, the long-term effects of later starts remain unresolved. In a pre-post design over 1 year, we studied a unique flexible school start system, in which 10–12th grade students chose daily between an 8:00 or 8:50AM-start. Missed study time (8:00–8:50) was compensated for … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 61 publications
1
3
0
1
Order By: Relevance
“…The fact that the relationship between school start time and school day sleep was unaffected by circadian preference did not support hypothesis 3, that students with later circadian preference would benefit more from later school start time compared with students with earlier circadian preference. However, previous findings have indicated that also morning type adolescents achieve substantially less sleep than recommended on school days (Saxvig, Evanger, et al, 2021), which may explain why also morning types, in line with previous research (Biller, Molenda, Zerbini, et al, 2022; Winnebeck et al, 2020), seemed to profit from later school start.…”
Section: Discussionsupporting
confidence: 60%
“…The fact that the relationship between school start time and school day sleep was unaffected by circadian preference did not support hypothesis 3, that students with later circadian preference would benefit more from later school start time compared with students with earlier circadian preference. However, previous findings have indicated that also morning type adolescents achieve substantially less sleep than recommended on school days (Saxvig, Evanger, et al, 2021), which may explain why also morning types, in line with previous research (Biller, Molenda, Zerbini, et al, 2022; Winnebeck et al, 2020), seemed to profit from later school start.…”
Section: Discussionsupporting
confidence: 60%
“…A study on adjusting school start times ( Owens et al, 2010 ) showed that starting high school 30 min later (8:30 a.m.) than usual (8:00 a.m.) improved students’ sleep duration and quality, thereby alleviating daytime drowsiness, fatigue, and depressed mood, while improving class attendance rate. In addition, implementing a flexible system in which students can choose to start school at 8 am or 9 am led to an improvement in their cognitive functions as well as sleep duration and quality ( Biller et al, 2022 ). Thus, school nurses should identify students with severe social jetlag and provide guidance and interventions to promote sleep hygiene and regular lifestyles.…”
Section: Discussionmentioning
confidence: 99%
“…Diversos estudios coinciden en que un retraso en dichos horarios repercutiría en una mejoría en la asistencia, reducción de la fatiga, disminución de las llegadas tarde, menor somnolencia diurna y mayor salud del sueño en general en los estudiantes (Albakri et al, 2021;Barnes & Drake, 2015;Boergers et al, 2014;Owens et al, 2010). Se ha observado que un retraso de 25 a 60 minutos otorga una mayor duración de sueño (Biller et al, 2022;Dunster et al, 2018) y puede reducir la depresión, la ingesta de cafeína y/o la dificultad para quedarse despierto (Minges & Redeker, 2016). Además, se ha visto que hay una mejora en el rendimiento académico cuando se retrasa el horario de ingreso escolar, gracias al alineamiento de la actividad escolar con el cronotipo típico de los adolescentes, especialmente en aquellos estudiantes que asisten al turno mañana (Goldin et al, 2020;Preckel et al, 2013;Rodríguez Ferrante et al, 2022).…”
Section: Sludges Y Sueñounclassified